Mental health of UK firefighters - Taylor A. M. Wolffe; Andrew Robinson; Anna Clinton; Louis Turrell; Anna A. Stec (Scientific Reports, 2023)
Abstract Exposure to trauma, high-stress situations, and disrupted sleep are well known risk factors affecting firefighters’ mental health. Little is known about the association between firefighters’ exposure to fire contaminants and mental health disorders. The UK Firefighter Contamination Survey assessed firefighters’ health and capacity for occupational exposure to contaminants. Participants were invited to anonymously complete its 64 questions online. Logistic regression analyses assessed the associations between self-reported mental health disorders and proxies of contaminant exposure. Results found that firefighters who notice soot in their nose/throat for more than a day after attending fires (Odds Ratio (OR) = 1.8, 1.4–2.4), and those who remain in their personal protective equipment (PPE) for over 4 h after fires (OR = 1.9, 1.2–3.1), were nearly twice as likely to report mental health disorders. Significantly increased odds ratios for all three outcomes of interest (anxiety, depression and/or any mental health disorders) were also found among firefighters who take PPE home to clean. Sleeping problems were reported by 61% of firefighters. These firefighters were 4.2 times more likely to report any mental health disorder (OR = 4.2, 3.7–4.9), 2.9 times more likely to report anxiety (OR = 2.9, 2.4–3.5) and 2.3 times more likely to report depression (OR = 2.3, 1.9–2.8) when compared to firefighters who did not report sleep issues. Effective decontamination measures within UK Fire and Rescue Services, together with firefighters’ wellness, may play a crucial role in protecting firefighters’ mental health.